2006
DOI: 10.1111/j.1944-9720.2006.tb02898.x
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' Use of English in Communicative German Language Classrooms: A Qualitative Analysis

Abstract: The use of English by foreign language teachers is a matter of much controversy. Whereas language switching by English‐speaking foreign language teachers has been the focus of previous research, relatively little is known about the amount of teachers' language use in the classroom when comparing native speakers of the foreign language with nonnative speakers. This qualitative study examined the amount and the purpose of English used by five teaching assistants (TAs) (three native speakers of English, one nativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 3 publications
0
15
0
2
Order By: Relevance
“…It should be noted that almost similar categories are found Kraemer's (2006) study on the use of English in German language classrooms and in a study by Hobbs et al (2010) on CS in Japanese classrooms. However, pre-imposed categories were not used in this study and not all categories present in such studies appear in ours.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…It should be noted that almost similar categories are found Kraemer's (2006) study on the use of English in German language classrooms and in a study by Hobbs et al (2010) on CS in Japanese classrooms. However, pre-imposed categories were not used in this study and not all categories present in such studies appear in ours.…”
Section: Discussionmentioning
confidence: 64%
“…They categorized cases of CS into functions such as 'classroom administrative vocabulary', 'grammar instruction', and 'classroom management'. Kraemer (2006) studied the amount and purpose of L1 use by five language teacher assistants, and reported that a "fair amount' of L1 was used, specifically for classroom management and translation. Hobbs et al (2010) compared CS behavior of native and non-native speaker teachers in Japanese language classrooms.…”
Section: Development Of Classroom Cs Researchmentioning
confidence: 99%
“…These uttered and inferred claims are in line with the literature regarding L1. Kraemer (2006), for instance, identifies eight functions for L1 use by teachers in L2 classes of which using L1 for classroom management is one of the most frequently stated purposes. Rolin-Ianziti and Brownlie (2002), too, as a part of their findings stated that teachers use L1 for classroom management.…”
Section: Ok I Said It In Farsi So That You Don't Forget It and Also mentioning
confidence: 99%
“…Encouraging and motivating student engagement in the foreign language classroom is challenging on multiple levels, not the least of which is overcoming perceptions of irrelevance in real-world applications. Additionally, learning languages is becoming increasingly more difficult because research suggests that foreign language teachers tend to not use the target language exclusively in the classroom (Kraemer, 2006), in effect discounting the notion of the Comprehensible Input hypothesis (Krashen, 1981). According to theory, learners improve and progress along a natural order when they receive consistent second language input that is one step beyond their current stage of linguistic competence.…”
Section: Introductionmentioning
confidence: 99%